Assessing consumption, emissions and costs of electrified vehicles under real driving conditions in a developing country with an inadequate road transport system. (August 2018) - Mansour, Charbel; Haddad, Marc; Zgheib, Elias
Highlights: Assessment of consumption, emissions and costs of electrified versus conventional vehicles. Construction of driving cycles representing real driving conditions in a developing country. HEV are the most beneficial for Lebanon in the near-term as no new infrastructure is required. PHEV and BEV contribute significant well-to-tank emissions due to the dirty electricity mix. Use of auxiliaries in congested traffic significantly reduce performance of electrified vehicles. Abstract: This study assesses the tank-to-wheel savings in fuel consumption and CO2 emissions as well as vehicle ownership and operating costs of electrified versus conventional midsize passenger vehicles in real-world driving conditions of the greater area of Beirut, Lebanon. This was done by developing representative driving cycles for typical home-to-work commutes during peak and off-peak traffic conditions based on an on-road travel survey. Results show that micro-hybrids are beneficial only in peak times, reducing consumption by 18.3%. Electrified vehicles provide substantial savings of 38.7% for hybrids and 88.6% for plug-in hybrids. However, plug-in and battery electric vehicles are found to contribute significant well-to-tank CO2 and pollutant emissions due to the dirty electricity mix in Lebanon. In addition, we find that the use of thermal comfort auxiliaries in congested traffic significantly reduces performance of electrified vehicles. Finally, an analysis of vehicle ownership and operating costs is done for the case of Lebanon and results show that hybrid electric vehicles are the preferred technology at low gasoline prices, while plug-in hybrids with a low electric range capability of 20 km become the most competitive at medium to high gasoline prices.